INVESTIGASI SIFAT MEKANIK MODEL BIODEGRADABLE STENT BERBASIS BAHAN PLLA - Muhammad Fadly Hi. Abbas; Sukiman B; Sandi Rais; Lita Asyriati Latif; Syarif Al Fajrin; Yulinda Sakinah Munim; Sahdar Rajak (Scientific Journal of Mechanical Engineering Kinematika, 2024)
Cardiovascular diseases are the leading cause of death worldwide, with diseases related to the narrowing of blood vessels being the primary cause of death in Indonesia. One solution for addressing this issue is the use of stents, specifically biodegradable polymer stents made from poly L-lactic acid (PLLA). The stent investigated in this study features a batik design (BT) with unidirectional struts (S><), combining open cell and close cell structures. This research employs a design analysis method using the finite element method (FEM) with the assistance of Abaqus student software. Data were collected by simulating the application of moments on each design combination of the stent in crimped and expanded configurations, with varying stent thicknesses of 120 µm, 130 µm, and 140 µm. The results indicate that, in the crimped configuration, the stent with a thickness of 130 µm produced the highest curvature index value, indicating the best flexibility. Meanwhile, in the expanded configuration, the stent with a thickness of 120 µm yielded the best flexibility results. This study makes a significant contribution to the development of more flexible and optimal biodegradable stents, with practical implications for improving stent design to reduce post-implantation complications and enhance clinical outcomes for patients with cardiovascular diseases.